2013
DOI: 10.1007/s11434-013-6032-7
|View full text |Cite
|
Sign up to set email alerts
|

Response of forest distribution to past climate change: An insight into future predictions

Abstract: Vegetation dynamics could lead to changes in the global carbon and hydrology cycle, as well as feedbacks to climate change. This paper reviews the response of forest dynamics to climate change. Based on palaeoecological studies, we summarized the features and modes of vegetation response to climate change and categorized the impacts of climate change on vegetation dynamics as three types: climate stress on vegetation, buffer effects by non-climatic factors, and perturbation of the vegetation distribution by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…The structure and position of alpine treelines are considered to be primarily thermally controlled (Körner 2012). In support of this hypothesis, global climatic warming has induced upward treeline encroachment and tree densification at some treeline ecotones (Camarero and Gutiérrez 2004;Chapin et al 2005;Liang et al 2011;Liu and Yin 2013;Greenwood et al 2014;Liang et al 2016;Wang et al 2016a). Many treelines globally, however, are relatively stable despite evidence of regional warming (Harsch et al 2009).…”
Section: Introductionmentioning
confidence: 90%
“…The structure and position of alpine treelines are considered to be primarily thermally controlled (Körner 2012). In support of this hypothesis, global climatic warming has induced upward treeline encroachment and tree densification at some treeline ecotones (Camarero and Gutiérrez 2004;Chapin et al 2005;Liang et al 2011;Liu and Yin 2013;Greenwood et al 2014;Liang et al 2016;Wang et al 2016a). Many treelines globally, however, are relatively stable despite evidence of regional warming (Harsch et al 2009).…”
Section: Introductionmentioning
confidence: 90%
“…Because low temperature often is the major constraint on tree regeneration, survival, and growth at alpine treelines (Wang et al. , Holtmeier and Broll , Liu and Yin , Renard et al. ), recent treeline densification at treelines has been linked to rising temperatures (Liang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Warmer conditions have been associated with increased tree regeneration and encroachment at treeline ecotones worldwide (Camarero & Gutiérrez, 2004;Liang et al, 2016;Liang, Wang, Eckstein, & Luo, 2011), and also with upward treeline shifts in many sites (Beckage et al, 2008;Du et al, 2018;Harsch et al, 2009;Huang et al, 2017;Peñuelas, Ogaya, Boada, & Jump, 2007). Changes in the patterns of distributional limits of tree species at treelines, however, are not homogenous and depend on many local-scale interactions (Camarero et al, 2017;Case & Duncan, 2014;Elliott, 2011;Kharuk, Ranson, Im, & Vdovin, 2010;Liu & Yin, 2013;Loranger, Zotz, & Bader, 2017;Wang, Camarero, Luo, & Liang, 2012;Wang, Liang, Sigdel, Liu, & Camarero, 2017;Zhu, Woodall, & Clark, 2012). For example, a global meta-analysis found that only about half of 166 treeline sites had shifted upward (Harsch et al, 2009), suggesting that the responses of alpine treelines to climatic warming are mediated by other factors such as biotic interactions (Harsch et al, 2012;Liang et al, 2016;Lyu, Zhang, Deng, & Mäkinen, 2016), geomorphic processes (Macias-Fauria & Johnson, 2013;Resler, Butler, & Malanson, 2005) or topography (Elliott & Cowell, 2015;Holtmeier & Broll, 2005;Li & Yang, 2004).…”
mentioning
confidence: 99%